Presentation of the results for deuterium retention and thermal release in a new type of low activation ferritic-martensitic steel EUROFER - Korica, Sanja Lj. (Vojnotehnički glasnik / Military Technical Courier, 2015)
This work presents the results of the investigation into deuterium retention and thermal release in low activation ferritic-martensitic steel EUROFER and its main components, Fe and Cr, using ion implantation, nuclear reaction depth profiling and the thermal desorption spectrometry technique.  The samples were exposed to deuterium ECR plasma of  6.5×1024 Dm-2 fluence. Our NRA results show that, at 300 K, most of deuterium is trapped in the near-surface region. A part of the implanted deuterium diffuses into the bulk and is trapped by defects beyond the implantation range. The results of the TDS measurement of the Cr sample confirm the formation of an ordered Cr-hydride phase.
Keywords: nuclear reactor materials; radiation efffects; Diffusion; nuclear resonances